Peningkatan Proses dan Hasil Belajar Pendidikan Agama Islam Melalui Metode Bernyanyi pada Siswa Kelas VIII SMP IT Andalas Cendikia - Dini Fitri Milenia; Sanja Trihardi; Ayu Vadilla; Aldi Syafri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Islamic Religious Education plays an important role in shaping students' religious personalities. However, in reality, IRE learning in junior high schools is still ineffective due to limited time allocation, only two hours per week, and the use of inappropriate methods. This condition has an impact on the low effectiveness of the learning process and student learning outcomes. As a solution, singing methods are applied to create a fun learning atmosphere so that students are more enthusiastic. This study aims to determine: (1) the improvement of the PAI learning process through the singing method in eighth-grade students at SMP IT Andalas Cendikia, and (2) the improvement of PAI learning outcomes through the singing method. The type of research used was Classroom Action Research (CAR) with 28 eighth-grade students as subjects. The research was conducted in three stages, namely pre-cycle, cycle I, and cycle II, with each cycle consisting of planning, implementation, observation, and reflection. Data analysis used the Kemmis and McTaggart model. The results showed that the singing method was able to increase student enthusiasm and learning outcomes. Learning enthusiasm increased from 64.28% in cycle I to 92.85% in cycle II, while student learning outcomes increased from 78.57% in cycle I to 100% in cycle II.